2020
DOI: 10.1039/c9nj05196a
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic framework/chitosan foams functionalized with polyethylene oxide as a sorbent for enrichment and analysis of bisphenols in beverages and water

Abstract: MIL-53(Al)/CS/PEO foam as a sorbent for the vortex assisted solid phase extraction of a trace amount of five bisphenols in beverages and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Given the interest of composites, researchers have started to merge MOF crystals with other materials, attempting to mitigate the weakest points of their single neat components through the combination of their best properties. Thus, different MOF-based composites and hybrid materials have been reported by incorporating them into inorganic materials (mesoporous silica) [ 21 , 22 ], polymers [ 23 , 24 ], metal oxide particles [ 25 , 26 ], and carbonaceous materials such as graphene oxide, carbon nanotubes, etc., [ 25 , 27 ]. This advance has made possible the design of sorbent materials with novel physicochemical features that lead to an enhancement of MOFs extraction performance by giving them higher structural support, by protecting their pores, or even by providing them with hydrophobicity and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the interest of composites, researchers have started to merge MOF crystals with other materials, attempting to mitigate the weakest points of their single neat components through the combination of their best properties. Thus, different MOF-based composites and hybrid materials have been reported by incorporating them into inorganic materials (mesoporous silica) [ 21 , 22 ], polymers [ 23 , 24 ], metal oxide particles [ 25 , 26 ], and carbonaceous materials such as graphene oxide, carbon nanotubes, etc., [ 25 , 27 ]. This advance has made possible the design of sorbent materials with novel physicochemical features that lead to an enhancement of MOFs extraction performance by giving them higher structural support, by protecting their pores, or even by providing them with hydrophobicity and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…This advance has made possible the design of sorbent materials with novel physicochemical features that lead to an enhancement of MOFs extraction performance by giving them higher structural support, by protecting their pores, or even by providing them with hydrophobicity and magnetic properties. Among these composites using polymers, those mostly used include chitosan [ 24 ], alginate [ 23 ], methacrylate derivatives [ 28 ], or polyvinylidene fluoride [ 29 ]. Composites made by MOFs and polystyrene (PS) have also been reported intending, from an inorganic chemistry point of view, the development of core-shell structures, mainly having PS beads as core, and MOFs coatings as shell [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of BPA and other bisphenols in beverages and water, a metal organic framework/chitosan/polyethylene oxide foam (MOFs/CS/PEO foam) was fabricated, where polyethylene oxide foam acts as a porogen to increase the adsorption capacity of the MOF [36]. After computations and experiments, MIL-53(Al)/CS/PEO was selected as a sorbent for a vortex assisted solid-phase extraction (VA-SPE), due to, for [38] with permission from Elsevier) example, its high surface area.…”
Section: Metal Organic Framework and Covalent Organic Frameworkmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), which are tunable porous materials, have attracted interest for gas storage, drug delivery, and catalysis because of their biomimetic catalysis properties and facile functional modification. , Previous studies have demonstrated that the type of MOF can greatly affect the immobilized enzyme efficiency. For example, Lyu et al embedded protein in MOF (ZIF-8), resulting in anti-cytochrome C (Cyt C) embedded in ZIF-8 showing a 10-fold increase in peroxidase activity compared to free Cyt c in solution, indicating that the enzyme is more active in ZIF-8 than in the free state.…”
Section: Introductionmentioning
confidence: 99%